Interface pressure distributions through structural modifications - Abu Bakar, A R.; Ouyang, H; Cao, Q (Society of Automotive Engineers, 2003)
Due to the friction forces acting at the rotor and pads interface, the pressure distribution at the interface is asymmetric in a disc brake system of normal floatingtype caliper design. The asymmetry and the high unevenness of the interface pressure distribution cause uneven wear and shorten life of pads. It has been speculated that these undesirable features promote disc brake squeal. This paper investigates the contact (interface) pressure distributions at the rotor and piston-pad interface in response to several ideas of simulated structural (geometric or material) modifications. These modifications are made on the pads and/or at the interface between the piston and the back plate or at the pad guide. A detailed finite element model is constructed taking into account all significant contact interfaces between disc brake components. Sliding frictional contact is analyzed to obtain the interface pressure distributions. A plausible modification is identified which offers improved interface pressure distributions against wear. This work may also help create a good design of disc brakes for improved noise performance as well.